2018
DOI: 10.2139/ssrn.3266899
|View full text |Cite
|
Sign up to set email alerts
|

School or Work?: The Role of Weather Shocks in Madagascar

Abstract: Études et Documents is a working papers series. Working Papers are not refereed, they constitute research in progress. Responsibility for the contents and opinions expressed in the working papers rests solely with the authors. Comments and suggestions are welcome and should be addressed to the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
2
3
0
Order By: Relevance
“…to support private consumption in doing consumption smoothing. This result is consistent with earlier studies showing that in the event of shocks, households try to reduce spending their children's education, especially girls, to make consumption smoothing (Marchetta et al, 2018;Cameron & Worswick, 2001). This result implies a low probability of girls to education attendance and high dropout rates high compared to boys.…”
Section: Robustness Checksupporting
confidence: 92%
“…to support private consumption in doing consumption smoothing. This result is consistent with earlier studies showing that in the event of shocks, households try to reduce spending their children's education, especially girls, to make consumption smoothing (Marchetta et al, 2018;Cameron & Worswick, 2001). This result implies a low probability of girls to education attendance and high dropout rates high compared to boys.…”
Section: Robustness Checksupporting
confidence: 92%
“…This result implies that weather shocks are associated with a lower probability of child school attendance, such that when the household experiences weather shocks, the probability of a child to attend school decreases by 18 percent. This finding share commonality with some previous studies that found a negative association between weather shocks and child school attendance (Adejuwon, 2016: Marchetta et al, 2018Millett & Shah, 2012;Agamile & Lawson, 2018). Weather shocks decrease child school attendance through two channels.…”
Section: The Effects Of Household Shocks On Child School Attendancesupporting
confidence: 90%
“…A number of studies in the literature have analysed the effects of household shocks on schooling in various countries. Marchetta and Tiberti (2018) conducted a study on weather shocks and school attendance in Madagascar. The study used the panel data set of years 2004 and 2011.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Street children in Antananarivo, Madagascar's capital city, were mostly deprived of any formal education due to economic activities and begging to secure their survival [49]. In some rural areas, more than half of the weekly time expenditure is dedicated to food acquisition [41], and households with fewer inhabitants are more vulnerable to internal or external stressors [50,51]. These so-called "shocks" consistently provoke a transition from school to work for adolescents and are primarily triggered by financial losses, diseases, death of family members [50], or extreme weather conditions [51].…”
Section: Environmental Education In Primary Schoolsmentioning
confidence: 99%
“…In some rural areas, more than half of the weekly time expenditure is dedicated to food acquisition [41], and households with fewer inhabitants are more vulnerable to internal or external stressors [50,51]. These so-called "shocks" consistently provoke a transition from school to work for adolescents and are primarily triggered by financial losses, diseases, death of family members [50], or extreme weather conditions [51]. Another major reason for considerably high drop-out rates can be found in the limited access to responsible family planning and contraceptives (e.g., condoms), promoting early childbearing and subsequently the drop-out of girls from the educational system [52,53].…”
Section: Environmental Education In Primary Schoolsmentioning
confidence: 99%